2017
DOI: 10.15761/crt.1000176
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosis of diabetic ketoacidosis as pelvic inflammatory disease in a Ghanaian teenager: A case report

Abstract: Misdiagnosis of diabetic ketoacidosis (DKA) among children and adolescents with diabetes is often misdiagnosed in clinical practice in Ghana, and it occurs at primary, secondary and tertiary care settings and among all grades of health practitioners. This is because DKA mimics many other disorders such as infections, surgical and obstetric emergencies and these conditions are more frequently seen in hospitals in Ghana than diabetes. It is, therefore, paramount that every child or adolescent presenting to a hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…DKA symptoms can mimic acute abdominal infection and per se cause abdominal pain and nausea. Misdiagnosis of DKA as PID has been reported [ 18 ]. It is not clear whether the patient's DKA was exacerbated by catecholamine production by the ileal tumor or whether her poorly controlled type I diabetes had led to DKA.…”
Section: Discussionmentioning
confidence: 99%
“…DKA symptoms can mimic acute abdominal infection and per se cause abdominal pain and nausea. Misdiagnosis of DKA as PID has been reported [ 18 ]. It is not clear whether the patient's DKA was exacerbated by catecholamine production by the ileal tumor or whether her poorly controlled type I diabetes had led to DKA.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical features also mimic acute infections such as cerebral malaria, meningitis and pneumonia [6,7]. Therefore, misdiagnosis of DKA as infections is possible and probably more common in African than has been reported [1,8,9]. Rwiza et al [8] reported misdiagnosis in Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, Kratzer [1] found out that all grades of health practitioners made wrong diagnosis such as malaria and typhoid fever instead of diabetes. Ameyaw et al [9] reported on a 19 year old female with undiagnosed T1D in DKA who was rather misdiagnosed as having pelvic inflammatory disease in hospital in Ghana. Missing diagnosis of DKA can have deleterious effect on the patient as the patient wrongly diagnosed would be mismanaged which could lead to further complications including mortality.…”
Section: Introductionmentioning
confidence: 99%